(untitled) (Circe de clásicos y modernos, 2018)
A. Brancacci (1990) has interpreted and rebuilt the philosophy of Antisthenes semantically, denying antisthenic nominalism and pointing out the binding status of the antisthenic method of philosophical research, which links rhetorical skill and moral knowledge. Brancacci’s interpretation has become canonical, but the antisthenic passages, which refer to the analysis of names, seem more an example of nominalist philosophy (according to the meaning that ‘nominalism’ acquired in the twelfth century disputes about status of universals) rather than an exclusively pattern for the semantic analysis of concepts.